Sphincter of Oddi botulinum toxin injection to prevent pancreatic fistula after distal pancreatectomy - Hackert, Thilo; Klaiber, Ulla; Hinz, Ulf; Kehayova, Tzveta; Probst, Pascal; Knebel, Phillip; Diener, Markus K.; Schneider, Lutz; Strobel, Oliver; Michalski, Christoph; Ulrich, Alexis; Sauer, Peter; et al. (Surgery, 2017)
Background: Postoperative pancreatic fistula represents the most important complication after distal pancreatectomy. The aim of this study was to evaluate the use of a preoperative endoscopic injection of botulinum toxin into the sphincter of Oddi to prevent postoperative pancreatic fistula (German Clinical Trials Register number: DRKS00007885). Methods: This was an investigator-initiated, prospective clinical phase I/II trial with an exploratory study design. We included patients who underwent preoperative endoscopic sphincter botulinum toxin injection (100 units of Botox). End points were the feasibility, safety, and postoperative outcomes, including postoperative pancreatic fistula within 30 days after distal pancreatectomy. Botulinum toxin patients were compared with a control collective of patients undergoing distal pancreatectomy without botulinum toxin injection by case-control matching in a 1:1 ratio. Results: Between February 2015 and February 2016, 29 patients were included. All patients underwent successful sphincter of Oddi botulinum toxin injection within a median of 6 (range 0-10) days before operation. One patient had an asymptomatic, self-limiting (48 hours) increase in serum amylase and lipase after injection. Distal pancreatectomy was performed in 24/29 patients; 5 patients were not resectable. Of the patients receiving botulinum toxin, 7 (29%) had increased amylase levels in drainage fluid on postoperative day 3 (the International Study Group of Pancreatic Surgery definition of postoperative pancreatic fistula grade A) without symptoms or need for reintervention. Importantly, no clinically relevant fistulas (International Study Group of Pancreatic Surgery grades B/C) were observed in botulinum toxin patients compared to 33% postoperative pancreatic fistula grade B/C in case-control patients (P < .004). Conclusion: Preoperative sphincter of Oddi botulinum toxin injection is a novel and safe approach to decrease the incidence of clinically relevant postoperative pancreatic fistula after distal pancreatectomy. The results of the present trial suggest its efficacy in the prevention of clinically relevant postoperative pancreatic fistula and are validated currently in the German Federal Government-sponsored, multicenter, randomized controlled PREBOT trial.